Severe Recurrent Necrotizing Myopathy in Pregnancy: A Case Report - Yue Li; Lingchao Meng; Yun Yuan; Lijuan Meng; Jing Lin; Bitao Bu (Frontiers in Neurology, 2018)
Pregnancy in patients with necrotizing autoimmune myopathy without identified antibodies is rarely reported. We report a case involving a 26-year-old woman with antibody-negative autoimmune necrotizing myopathy who experienced a relapse during pregnancy. Before pregnancy, the patient's myopathy symptoms and elevated serum creatine kinase levels had been successfully controlled with oral prednisone and tacrolimus for 1 year. However, she discontinued the therapy on her own accord, with the aim of conceiving. During pregnancy, she experienced a very severe relapse of muscle weakness and dyspnea and her creatine kinase level increased to >8,000 U/L. After she was treated with intravenous immunoglobulin, oral prednisone, and tacrolimus, she slowly recovered and delivered a healthy neonate. She continues to take oral tacrolimus (3 mg/day) and has remained symptom-free 2 years later.